IMPLEMENTASI METODE MIND MAPPING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AHLAK MA MIFTAHUL ULUM AN-NUR PROBOLINGGO - Fitrianingsih Wulandari; Suna; Pratiwi Dwi Warih Sitaresmi (Fakultas Agama Islam Universitas Wiralodra, 2022)
This research aims to find out: 1) student learning outcomes before and after using the Mind Mapping method 2) improvement of the learning outcomes of IAGA class XI Students through the use of mind mapping methods in moral faith lessons on material avoiding the major sins. This research is a class action research (PTK) that is carried out in cycles stages, while each cycle consists of four stages, namely planning, implementation, observation and reflection. Subjects were taken as many as 14 students precisely in class XI IAGA. The data collection technique in this study through observation, interview and tests of learning results at the end of each cycle. The results of this study showed that there is an increase in learning outcomes in students. This is shown by the comparison of the average learning outcomes achieved in the pre-cycle 70.57 with a percentage of 35.71%, cycle I 77.5 with a percentage of 50%, cycle II 85.71 with a percentage of 85.71%. The increase show that the use of mind mapping learning methods is able to improve students' learning outcomes.